Near-infrared cyclometalated iridium(iii) complexes with bipolar features for efficient OLEDs via solution-processing. Issue 25 (18th June 2020) - Yu, Junting; Li, Maoqiu; Xu, Chao; Meng, Fanyuan; Cao, Jiamin; Tan, Hua; Zhu, Weiguo
Abstract : Double gain, a bipolar feature NIR iridium(iii ) complex with both hole and electron transporting group to improve the OLED performance. Abstract : A novel bipolar NIR iridium(iii ) complex (CH3 OTPA-BTz-Iq)2 Ir(pic-OXD) with both a hole transporting (HT) triphenylamine (TPA) group and an electron transporting (ET) oxadiazole (OXD) group was designed and synthesized. It was observed that the incorporation of OXD and TPA into the ligand (CH3 OTPA-BTz-Iq)2 Ir(pic-OXD) improved the optophysical and electroluminescence performance in comparison with the parent iridium(iii ) complex (CH3 OTPA-BTz-Iq)2 Irpic. In (CH3 OTPA-BTz-Iq)2 Ir(pic-OXD)-based OLEDs, a maximum external quantum efficiency (EQEmax ) of 1.15% at 716 nm was obtained, which is much superior than that of the (CH3 OTPA-BTz-Iq)2 Irpic-based OLEDs (0.41% at 723 nm).